Cardiovascular Effects of Adding Adrenaline to Arthroscopic Knee Irrigation Fluid in Canine Diagnostic Procedures - Ana Zapata; Claudio Iván Serra Aguado; José Ignacio Redondo; José Román Soto Muñoz; José Sansano-Maestre; Rocío Fernández-Parra (Animals)
Background: Adrenaline is used as a local haemostatic in human arthroscopy, due to its peripheral vasoconstrictive properties, which enhance image quality with minimal cardiovascular side effects. This study aims to evaluate the effects of adrenaline in arthroscopic irrigation fluid and asses its impact on image visibility. Methods: A prospective, double-blind, randomised clinical trial was conducted on 20 knees from 18 dogs undergoing diagnostic arthroscopies. Dogs were randomly assigned to two groups: group A (received lactate Ringer (LR) with adrenaline 0.33 mg L−1) and group C (received LR with 0.33 mL of saline solution). Cardiovascular parameters were recorded using a multiparametric monitor, with advanced hemodynamic parameters assessed using the PRAM method (MostCare®) in half of the dogs, and glucose, cortisol, and adrenaline levels were measured at various time points. Hemoglobin concentration was calculated based on the residual fluid and image quality was evaluated by a blinded surgeon using a visual analog scale (VAS). Results: No significant differences between groups in cardiovascular parameters, glucose, cortisol, adrenaline, hemoglobin, or VAS scores; only time differences for cortisol and adrenaline. Conclusions: The use of adrenaline at 0.33 mg L−1 in arthroscopic irrigation fluid does not cause significant cardiovascular changes or improve image quality, confirming it is safe at this concentration.